PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATERI TRANSFORMASI ENERGI DI SEKITAR KITA MELALUI MODEL PROBLEM BASED LEARNING DI KELAS IV UPTD SD INPRES LASIANA KOTA KUPANG - Putri Lay Kudji; Dr. Taty R. Koroh; Maxsel Koro (STKIP Subang, 2025)
Thesis by Putri Lay Kudji Student ID: 1901140354 (2025) PGSD. With the title Improving Student Learning Outcomes on the Energy Transformation Around Us Material Through the Problem-Based Learning Model in Grade IV of the UPTD SD Inpres Lasiana, Kupang City. The research problem is how the application of the Problem Based Learning Model on the Energy Transformation Around Us material can improve student learning outcomes. This study aims to determine how using the Problem-Based Learning Model can improve science learning outcomes on the Energy Transformation Around Us material in Grade IV of the UPTD SD Inpres Lasiana, Kupang City. The type of research used was Classroom Action Research (CAR), implemented in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were 30 fourth-grade students in the even semester of the 2024/2025 academic year. The results showed that the application of the Problem Based Learning model can improve student learning outcomes. In the first cycle, of the 30 students, 23 (76.7%) completed the lesson and 7 (23.3%) did not complete the lesson. Then, there was an increase in cycle II, with 28 students completing the course (93.3%) and 2 students failing (6.7%). Therefore, it can be concluded that the implementation of the Problem Based Learning model is effective in improving the learning outcomes of fourth-grade students at the UPTD SD Inpres Lasiana, Kupang City.